Strategic B2B customer experience management: the importance of outcomes-based measures - Zolkiewski, Judy; Story, Victoria; Burton, Jamie; Chan, Paul; Gomes, Andre; Hunter-Jones, Philippa; O’Malley, Lisa; Peters, Linda D.; Raddats, Chris; Robinson, William (Emerald, 2017)
Purpose